Pemerolehan Bahasa Pertama Anak dalam Aspek Fonologi, Morfosintaksis, Leksikon, dan Pragmatik - Fariza (Hikamatzu | Journal of Multidisciplinary, 2026)
This article analyzes first language acquisition in children through four linguistic domains: phonology, morphosyntax, lexicon, and pragmatics. The study responds to the tendency of previous discussions to separate sound production, grammatical development, vocabulary growth, and communicative use, although these domains develop in a connected way during early childhood. This research uses a descriptive qualitative design with a psycholinguistic perspective and document analysis of two source texts on first language acquisition. Data were reduced, coded, and classified into phonological, morphosyntactic, lexical, and pragmatic categories, then interpreted through recent studies in child language development. The findings show that phonological acquisition appears first through dominant vowels [a], [i], and [e], early consonants [b], [p], [m], [n], and [t], and simple syllable patterns such as CV, CVC, and CVCV. Morphosyntactic acquisition develops from one-word and two-word utterances to simple sentences, while lexical acquisition expands through repeated exposure to people, objects, actions, and qualities in the child's environment. Pragmatic acquisition is reflected in requesting, rejecting, calling, informing, and adjusting speech to interlocutors. The study concludes that these four domains should be understood as an integrated developmental process strengthened by responsive family interaction.